Training as an Effective Method of Practical Training of Biological Students - Fishchuk, Oksana (Psychological Prospects Journal, 2020)
Modernization of education in Ukraine in accordance with modern requirements actualizes the study of the training form of work for students of different specialties. The goals, tasks and advantages of using trainings in the educational process are considered. A specialist in the field of biology has ample employment opportunities (from laboratories and horticultural farms, to ecological tourism). We consider training as the best method for the development of highly specialized professional skills (hard skills) and skills of interpersonal interaction (soft skills) for a biology student. The structure of educational training for students of biologists is offered. The main purpose, tasks and three thematic blocks of training are described. The first is aimed to understanding the importance of the profession, a holistic view to a particular activity. The second is aimed to developing specific professional skills and abilities. The third is focused on the participants’ awareness of themselves in the system that becomes part of their activities and the optimization of relations to this system. The use of training in classes on the topic: «Structure and functions of the flower» for biology students is described. In the training we used the method of group discussion. The training within the course «Plant Biomorphology» is aimed at developing biology students hard skills (repetition and systematization of knowledge about flower structure, flower functions and fruit structure) and soft skills (ability to work in a group, establish interpersonal interaction, division of responsibilities, definition leader). Prospects for the study are seen in the full development and testing of training for students of biology.